1986
DOI: 10.1016/0304-3959(86)90048-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thermal stimulation on clinical and experimental itch

Abstract: In order to substantiate accidental observations on the influence of skin temperature on itch, and to elucidate a possible involvement of thermoreceptors in itch generation, the effects of thermostimulation on clinical and experimental itch were studied. Eighteen patients with atopic dermatitis rated the intensity of spontaneous itch on one of their forearms before, during, and after its immersion in a waterbath of either 10 degrees C or 45 degrees C. In 40 normal subjects itch was elicited by histamine topica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
1
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 22 publications
9
61
1
1
Order By: Relevance
“…An additional surprising result in the present study was that noxious heat (45°and 50°C) and cold (20°, 15°, and 10°C), stimuli that are also known to reduce itch in humans (Fruhstofer et al 1986;Murray and Weaver 1975;Ward et al 1996;Yosipovitch et al 2005Yosipovitch et al , 2007, failed to reduce mean pruriceptive firing levels during or after application of the thermal stimuli.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…An additional surprising result in the present study was that noxious heat (45°and 50°C) and cold (20°, 15°, and 10°C), stimuli that are also known to reduce itch in humans (Fruhstofer et al 1986;Murray and Weaver 1975;Ward et al 1996;Yosipovitch et al 2005Yosipovitch et al , 2007, failed to reduce mean pruriceptive firing levels during or after application of the thermal stimuli.…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, application of either noxious cold (Fruhstorfer et al 1986;Melton and Shelly 1950;Mochizuki et al 2003;Murray and Weaver 1975;Simone et al 1991;Yosipovitch et al 2005) or noxious heat (Ward et al 1996;Yosipovitch et al 2005Yosipovitch et al , 2007 has been shown to reduce itch. Mixed effects of noxious heat on itch also have been reported; immersion of itchy skin in 45°C water reduced itch in two-thirds of subjects, whereas itch was increased in the remaining subjects (Fruhstofer et al 1986). Electrical stimulation at levels sufficient to induce pain also can reduce itch (Bickford 1938;Nilsson et al 1997;Ward et al 1996).…”
mentioning
confidence: 99%
“…The units described in this paper were in part CH; i.e., they were also excited by heating the skin in the range of 41-46°C and also by capsaicin application. This is interesting from a clinical point of view, because it is known that warming often enhances itch (Fruhstorfer et al, 1986). On the other hand, these histamine-sensitive CH units do not necessarily contribute to the sensation of warmth or burning caused by heat or capsaicin application, which is probably mediated by the large population of CM H and CH units with little histamine sensitivity.…”
Section: Discussionmentioning
confidence: 98%
“…Another property that might be expected of a pruriceptive neuron is that its activity is increased by stimuli that increase the sensation of itch, for example, warming the skin (Fruhstorfer et al 1986) or spinal administration of opiates (Ballantyne et al 1988;Ko and Naughton 2000). In addition, central pruriceptive neurons should become sensitized to the mechanical stimuli that evoke enhanced itch in areas of alloknesis and hyperknesis after application of a pruritic chemical Bickford 1938;Simone et al 1991Simone et al , 1991a.…”
Section: Neuronal Response Properties That Might Contribute To Itch Amentioning
confidence: 99%